CONSTRUCTIVISM BASED E-LEARNING: A BIBLIOMETRIC ANALYSIS USING VOSVIEWER - Vyas, Gautamkumar H; Rathod, Harishchandra Singh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The concept of learning by doing in this digital era is of great importance for educational institutes as well as corporates. The purpose of this paper is to provide an extensive bibliometric literature review on 'constructivism’ and ‘e-learning’. Total 107 articles found in the Scopus database ranging from 2011 to 2021 were analyzed in this study. In this, study literature has been classified and visualized using VOSviewer software. This study has provided a keyword network, text data network, and network of countries where research on these topics has been carried out through visualizations. Overall, this review provides an appropriate reference point for further research on ‘Constructivism’ and ‘e-learning’.